STUDY OF THE ANTIHYPOXIC EFFICIENCY OF SUCCINATE UNDER THE CONDITIONS OF METHEMOGLOBINEMIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Modeling of methemoglobinemia (MetHb) led to a violation of antioxidant protection, which was manifested by a decrease in the activity of enzymes of the primary link of the antioxidant system – superoxide dismutase and catalase in blood plasma and brain homogenates of experimental animals. The state of MetHb also led to an increase in the concentration of malondialdehyde, an indicator of lipid peroxidation, as well as an indicator of oxidative modification of proteins. It has been established that the antihypoxic activity in the application of succinic acid significantly suppresses the biochemical changes caused by the hypoxic state.
Keywords: methemoglobinemia; antihypoxic activity; succinic acid